2022
DOI: 10.1111/1744-7917.13109
|View full text |Cite
|
Sign up to set email alerts
|

BmCaspase‐8‐like regulates autophagy by suppressing BmDREDD‐mediated cleavage of BmATG6

Abstract: Autophagy plays an important role in tissue remodeling during insect development. The interplay between autophagy‐related (ATG) proteins and caspases regulates the autophagic activity of ATGs, thereby modulating the process of autophagy. Our previous study characterized BmCaspase‐8‐like (BmCasp8L) as a caspase suppressor that inhibits apoptosis and immune signaling by suppressing the activation of death‐related ced‐3/Nedd2‐like caspase (DREDD), a caspase‐8 homolog in silkworm. In this study, we explored the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The Caspase-8-like gene, which is the most similar to caspase 8, is considered to function as an initiator caspase and plays crucial roles in extrinsic apoptotic pathways in some mollusk species [4,8]. However, some researchers found that caspase-8-like worked as a caspase suppressor to inhibit apoptosis and immune signaling in silkworm (Bombyx mori) [9]. The contradiction in this research implies that functional differences in caspase-8-like exist in different invertebrates.…”
Section: Introductionmentioning
confidence: 70%
“…The Caspase-8-like gene, which is the most similar to caspase 8, is considered to function as an initiator caspase and plays crucial roles in extrinsic apoptotic pathways in some mollusk species [4,8]. However, some researchers found that caspase-8-like worked as a caspase suppressor to inhibit apoptosis and immune signaling in silkworm (Bombyx mori) [9]. The contradiction in this research implies that functional differences in caspase-8-like exist in different invertebrates.…”
Section: Introductionmentioning
confidence: 70%